2008
DOI: 10.1101/gad.483308
|View full text |Cite
|
Sign up to set email alerts
|

Sus1 is recruited to coding regions and functions during transcription elongation in association with SAGA and TREX2

Abstract: Gene transcription, RNA biogenesis, and mRNA transport constitute a complicated process essential for all eukaryotic cells. The transcription/export factor Sus1 plays a key role in coupling transcription activation with mRNA export, and it resides in both the SAGA and TREX2 complexes. Moreover, Sus1 is responsible for GAL1 gene gating at the nuclear periphery, which is important for its transcriptional status. Here, we show that Sus1 is required during transcription elongation and is associated with the elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 48 publications
(63 reference statements)
5
129
3
Order By: Relevance
“…Together with gene localization experiments, these observations indicate that SAGA and TREX2 act synergistically to recruit Sus1 to chromatin, and to promote gene-NPC anchoring (Jani et al, 2009;Kohler et al, 2006;Pascual-Garcia et al, 2008). In light of these findings and because of the earlier observation that the interaction of Nup2 with GAL gene promoters does not require SAGA components (Schmid et al, 2006), it is conceivable that gene repositioning to the NPC occurs mainly in two steps: the interaction of specific promoter-bound transcription activators with nucleoporins mediates the initial binding to the NPC, whereas the subsequent recruitment of SAGA might stabilize gene-NPC anchoring by interacting with TREX2 at a minimum.…”
Section: Box 1 Schematic View Of Npc Structure and Compositionmentioning
confidence: 90%
See 1 more Smart Citation
“…Together with gene localization experiments, these observations indicate that SAGA and TREX2 act synergistically to recruit Sus1 to chromatin, and to promote gene-NPC anchoring (Jani et al, 2009;Kohler et al, 2006;Pascual-Garcia et al, 2008). In light of these findings and because of the earlier observation that the interaction of Nup2 with GAL gene promoters does not require SAGA components (Schmid et al, 2006), it is conceivable that gene repositioning to the NPC occurs mainly in two steps: the interaction of specific promoter-bound transcription activators with nucleoporins mediates the initial binding to the NPC, whereas the subsequent recruitment of SAGA might stabilize gene-NPC anchoring by interacting with TREX2 at a minimum.…”
Section: Box 1 Schematic View Of Npc Structure and Compositionmentioning
confidence: 90%
“…Reinforcing the view that transcription elongation events contribute to gene-NPC gating, it was reported that the export factor Sus1 is loaded on the elongating machinery through interaction with the phosphorylated CTD of RNA Pol II, and that it functions with SAGA and TREX2 not only during transcription initiation but also during elongation (Faza et al, 2009;GonzalezAguilera et al, 2008;Govind et al, 2007;Pascual-Garcia et al, 2008;Wyce et al, 2007). Notably, TREX2 mutants exhibit defects in transcription elongation as well as enhanced transcriptiondependent hyper-recombination.…”
Section: Gene-npc Anchoring and Coordination Of Mrnp Biogenesis Durinmentioning
confidence: 99%
“…Intriguingly, recent studies in yeast have also implicated the coupling of transcriptional initiation machinery with mRNA export. 15,[58][59][60] In these studies, Sus1 has been identified to link the co-activator SAGA complex with the TREX-2 complex (which consists of the subunits Sac3, Thp1, Cdc31 and Sus1). TREX-2 interacts with NPC via nucleoporins, Nup1 and Nup60.…”
mentioning
confidence: 99%
“…Importantly, as observed for conventional elongation factors, the association of Vps proteins with ARG1 or GAL1 CDS was strongly dependent on target gene transcription, occurring at high levels only under conditions where the relevant transcriptional activators are induced (Gcn4) or functional (Gal4). In addition, the TATA promoter element is required for high-level Vps15 and Vps34 occupancies at ARG1 under inducing conditions, and Vps15 and Vps34 occupancies of ARG1 CDS were stimulated by the Pol II CTD kinase Cdk7/ Kin28-a characteristic of numerous factors involved in cotranscriptional histone modifications, mRNA processing or nuclear export, and the elongation or termination phases of transcription (Phatnani and Greenleaf 2006;Govind et al 2007;Pascual-Garcia et al 2008;Ginsburg et al 2009;Govind et al 2010;Qiu et al 2012).…”
Section: Discussionmentioning
confidence: 99%